Hybridisation between White-faced and Fulvous Ducks in the wild: further evidence from South Africa - Harebottle, Doug; Vanderwalt, Brian (Biodiversity Observations, 2014)
In southern Africa, little is known about hybridisation between indigenous duck species in the wild and there are few reported and/or documented cases...